The Critical Role of School Nurses: Supporting Health, Education, and Social Equity for Students with Disabilities - Zahra Saboohi; Fatemeh Guderzi (Iranian Journal of Medical Sciences)
This letter underscores the vital role that school nurses play in providing equal educational opportunities for students with disabilities.